2007
DOI: 10.4012/dmj.26.613
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Resin Composite Materials Relative to Biofilm Formation

Abstract: The surface properties of three different resin composite materials which influence Streptococcus mutans biofilm formation were evaluated using an artificial mouth system (AMS). Specimens were prepared from Clearfil AP-X, Grandio, and Reactmer Paste, and each material was divided into two groups: (1) surface was ground with 800-grit silicon paper (SiC#800); or (2) surface was polished with up to 1-μm diamond paste (DP1μm). Biofilms were grown on the surface of each specimen for 20 hours, and then subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 32 publications
(29 reference statements)
4
76
2
4
Order By: Relevance
“…Other investigators state that polished composite surfaces supported larger amounts of plaque due to the loss of superficial filler particles during the polishing process 4,25,50,52) . These observations contradict those of other authors who found that surface polishing of composite materials rendered the materials more plaque resistant and that the procedure was important to reduce bacterial accumulation 8,37,45) . The use of air-polishing devices in oral hygiene and periodontal therapy has proven to be a very effective means in rapidly removing stains and dental plaque 10) .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Other investigators state that polished composite surfaces supported larger amounts of plaque due to the loss of superficial filler particles during the polishing process 4,25,50,52) . These observations contradict those of other authors who found that surface polishing of composite materials rendered the materials more plaque resistant and that the procedure was important to reduce bacterial accumulation 8,37,45) . The use of air-polishing devices in oral hygiene and periodontal therapy has proven to be a very effective means in rapidly removing stains and dental plaque 10) .…”
Section: Discussioncontrasting
confidence: 57%
“…Thus a smooth surface with low surface free energy is important to modulate biofilm adherence and growth. An improvement in surface conditions could be achieved if resin composites were carefully polished 8,29,37,45) . In addition, biofilm formation is also influenced by the type (chemical composition) of resin biomaterial 3,24,[45][46][47] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural gloss and final esthetic of the restoration, abrasivity and wear kinetics 1) ; improved mechanical properties 2) ; and tactile perception and comfort of the patient 3) are highly associated with surface properties. Moreover, smooth surfaces and margins reduce the risk of biofilm adhesion and maturation, recurrent caries, gingival irritation [4][5][6][7][8] and staining 9) . The smoothest possible surface is obtained when the resin composite polymerizes against a Mylar matrix without subsequent finishing or polishing 10,11) ; however, such a surface has a resin-rich layer, poor mechanical properties, is susceptible to increased wear and discoloration and should be eliminated 2,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, if surfaces with controlled wetting properties could be fabricated, then the quest for contamination-free surfaces would become a long-awaited reality 1) . From the manufacturing perspective of dental materials, several methods have been proposed for the development of restorative materials [2][3][4] and adhesive materials 5,6) with an ability to influence oral biofilm formation. Development of dental materials possessing "self-cleaning" surface property would bring a dramatic change to the field of clinical dentistry.…”
Section: Introductionmentioning
confidence: 99%